Influence of phosphorus doping on surface chemistry and capacitive behaviors of porous carbon electrode. (10th March 2018) - Ma, Weiping; Xie, Lijing; Dai, Liqin; Sun, Guohua; Chen, Jianzhong; Su, Fangyuan; Cao, Yufang; Lei, Hong; Kong, Qingqiang; Chen, Cheng-Meng
Abstract: Heteroatom doping is an effective strategy to modify the surface properties of carbon electrode, thus boosting its electrochemical performance. In this work, phosphorus (P)-doped porous carbons with high specific surface are prepared by KOH pre-activation of ultrapure anthracite and further H3 PO4 activation. H3 PO4 post-activation not only generates more mesoporous for a rapid ion diffusion, but also provides potential P-source for the P-doping on carbon scaffold. The increase of P-doped content significantly restrains the formation of unstable quinone and carboxylic groups, and then enhances oxidation stability of P-doped porous carbon. When evaluated as electrodes in 1 m Et4 NBF4 /PC, the resultant material exhibits excellent rate capability of 75% retention at 30 A g −1, extraordinary stability of 90% capacitance retention after 20000 cycles and low leakage current of less than 1.2 μA. More importantly, due to the blockage of active oxidation sites by phosphate groups, the P-doped porous carbon can stably operate at higher voltage of 3.0 V in Et4 NBF4 /PC compared to that of undoped porous carbon, so as to deliver a high energy density of 38.65 Wh kg −1 at 1500 W kg −1 . The study offers insightful material chemistry for industrial application of H3 PO4 activated porous carbon in advanced electrochemical energy storage. Graphical abstract: Image 1 Highlights: Phosphate groups on the carbon scaffold effectively block the active oxidation sites. The optimized P-doped carbon demonstrates a mesoporous rate of even up to 87.48%. P-doped carbon retains as high as 90.2% of initial capacitance over 20000 cycles. High-voltage cycling stability and energy density are significantly improved.